Effect of Banana Peel Slurry on The Microbiological and Chemical Properties of Gebang Sap as well as Physical and Organoleptic Properties of Liquid Sugar - Lalel, Herianus J. D.; Rubak, Yuliana Tandi; Nalle, Ryan P.I.; Saingo, Silvia Marise (Food Scientia: Journal of Food Science and Technology, 2024)
Gebang (Corypha utan Lamk) sap is one of the raw materials for making liquid sugar in Timor Island. The sap is easily to be fermented by contaminant microbes which lowering its quality. Therefore, it needs a study to know the potency of banana peel as a safe preservative for gebang sap. A study has been conducted using a simple Completely Randomized Design (CRD) with 4 treatments: control (A0); 5% banana peel slurry (A1); 10% banana peel slurry (A2); 15% banana peel slurry (A3) repeated 3 times. The parameters observed were total microbes, acidity (pH) and total soluble solids (TSS) of the sap as well as water activity and liquid sugar organoleptic. The results showed that the treatment of adding banana peel slurry to gewang nira was able to affect the chemical and microbiological properties of gebang sap as well as the physical and organoleptic properties of liquid sugar. Based on chemical and microbiological properties of the sap, the best treatment was found in 15% of banana peel slurry treatment (A4). The treatment (A4) also gave the best physical properties of liquid sugar. While based on organoleptic properties the sugar, the best treatment was shown in the treatment of 5% banana peel slurry.